Strategi Komisi Pemilihan Umum (KPU) Kabupaten Jember dalam Persiapan Pemilu Tahun 2024 - Arsya, Khafid; Adawiyah, Putri Robiatul (Buletin Antropologi Indonesia, 2024)
The purpose of this research is to find out what strategies have been prepared by the General Election Commission (KPU) of Jember Regency in preparing for the upcoming 2024 elections. In addition, this study also aims to determine the factors that support and also factors that hinder the implementation of the strategy that has been prepared by the General Election Commission (KPU) of Jember Regency. The method used is a descriptive qualitative method. In this study, several informants were interviewed in order to obtain valid data. The results of this study indicate that: The General Election Commission (KPU) of Jember Regency already has a strategic plan that will take effect from 2020 to 2024, and the strategy that has been made by the Jember Regency KPU is divided into 2 (two) strategies, the first strategy is based on the strengths and opportunities possessed by the Jember Regency KPU, the two strategies are based on the weaknesses and threats possessed by the Jember Regency KPU. There are 2 (two) supporting factors owned by the Jember Regency KPU, namely, the first human resource factor that supports carrying out the KPU strategy, the second is facilities and infrastructure, and there are approximately 10 inhibiting factors which also pose a threat to the KPU in carrying out the strategy.